Technical Considerations For The Design And Construction Of Mine Seals To Withstand Hydraulic Heads In Underground Mines - D. T. Kirkwood (Society for Mining, Metallurgy & Exploration, 1995)
The practice of impounding mine water and liquid fine waste in underground mines is increasing. Often these underground impoundments are created by constructing seals or bulkheads designed to withstand the expected hydraulic pressures. Occasionally seals are built for another purpose, usually to act as explosion-resistant ventilation barriers. Due to factors such as clogged drain pipes or unexpectedly high inflow rates, these explosion-resistant seals sometimes become subjected to hydraulic pressures. The incidence of seal failures due to inadequate design and/or construction is also on the increase. Fortunately, to date, no lives have been lost by water seal failures, but a clearer understanding of the design and construction considerations specific to water seals is vital to keep this from occurring in the future. This paper presents technical considerations for the design and construction of seals which will specifically be required to withstand hydraulic pressures in underground mines.